Procurement Of Symphysis Block Graft Using Dynamic Navigation: Accuracy Analysis - S, Hamitha; Selvaganesh, Sahana; Nesappan, Thiyaneshwar (Journal of Neonatal Surgery, 2025)
Background: In order to restore bone volume in atrophic alveolar ridges, ridge augmentation is an essential operation in dental implantology. Conventional techniques, however beneficial, frequently provide difficulties with accuracy and productivity. With the introduction of dynamic navigation systems to dentistry, there is a chance to improve the precision and results of ridge augmentation operations. With the use of dynamic navigation technology, the accuracy of procuring the block graft is both feasible and accurate. Materials and Methods: Cadaver mandibles with inadequate alveolar ridges were chosen. The ridge augmentation procedure was led by a dynamic navigation system. A 3D model of the mandible was created using CBCT images for preoperative planning, and the navigation system was incorporated with it. During the augmentation process, real-time tracking and feedback were given by the navigation system during block graft procurement. Results: The dynamic navigation system significantly improved the precision of block graft procurement where there was significance in the Apex angular deviation (p value < 0.00) which is important as the underlying vital structures can be properly visualized under Dynamic navigation. Real-time feedback allowed for accurate placement of bone grafts, closely adhering to the preoperative plan. Postoperative CBCT scans confirmed the accuracy of the augmentation, with minimal deviation from the planned augmentation sites. Conclusion: The precision and predictability of ridge augmentation in cadaver mandibles can be improved with the use of dynamic navigation technology, as this proof-of-concept study shows. The use of dynamic navigation into clinical practice has promise for enhancing surgical outcomes and mitigating problems linked to conventional ridge augmentation techniques.